Tutors and trainees’ perception of the effectiveness of the vocational and entrepreneurial skill acquisition programme in Ogun State tertiary institutions (2013)
The quality of Nigerian graduates has continued to be a major concern to stakeholders in education. The prevalence of half baked graduates from tertiary institutions in Nigeria has led to astronomical increase in the unemployed graduates in the society. In order to curb the menace of unemployment among graduates in Nigeria, some tertiary institutions have integrated the teaching and learning of vocational and entrepreneurial skill acquisition programme into their regular academic programme. This study investigated tutors and trainees' perception of the effectiveness of the vocational and entrepreneurial skill acquisition programme in Ogun State tertiary institutions. The subjects of the study included trainees and vocational tutors. 534 randomly selected trainees and 58 tutors from two tertiary institutions in Ogun State who offer vocational and entrepreneurial skill acquisition programme were used for the study. The study utilizes questionnaires and a rating scale as instruments to gather data from the trainees and tutors. The obtained data were analysed using descriptive and inferential statistics (mean, standard deviation and t-test). The study revealed that financial resources disbursed for the effectiveness of the programme were found to be moderately adequate and utilized. It was also revealed that there is a statistical significant difference in trainees' skill acquisition in computer-science/maintenance, livestock poultry management and fashion designing since the inception of the programme. However, the study revealed that the human resources available for the programme are not adequate. Some of the recommendations made were that more tutors and non-teaching staff should be employed, faulty or worn-out facilities/equipment should be repaired or replaced and financial resources allocated to the vocational department should be reviewed upward and monitored to ensure purposeful and judicious use of such.